If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(y + 3) = 40 Reorder the terms: 10(3 + y) = 40 (3 * 10 + y * 10) = 40 (30 + 10y) = 40 Solving 30 + 10y = 40 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 10y = 40 + -30 Combine like terms: 30 + -30 = 0 0 + 10y = 40 + -30 10y = 40 + -30 Combine like terms: 40 + -30 = 10 10y = 10 Divide each side by '10'. y = 1 Simplifying y = 1
| 4-3*-5=Y | | 240+0.15x=357 | | 3(4-5m)-12+(-3m)= | | -4-5y=7 | | 3+6x=6-7x | | 18-3x=-22 | | 43+2x=7x+16 | | 10X-40=-10 | | x^4-5x^3-3x^2+13x+10=0 | | 3x+5=95+6 | | 5z-3=2z+9 | | 5p-3=0 | | [7x-7]+3=4x+1 | | f(x) = 7 ( 10 )x+ 1 | | 4p^2+8p^3=0 | | 8i(7-9i)=0 | | 6+2u=-2 | | 2(2s+2)=2s+2s+4 | | e^3x+7=e^2 | | 1.4x(5x-4)=-1.4 | | 10x+9x=76 | | x=-4x+25 | | 14-93=49-57a | | 7x-25=49 | | 6=3x^2-3x+6 | | 4(x^4-3x^2+8)= | | 5n+3=3n+1 | | 10x+4x+8=8x+2x+48 | | 4x+6-x=18+x | | N^2+6-20=0 | | 5(2x-3)=8(x+2) | | x^2+5x+6=y |